Optimalisasi Keuntungan Chai Kue Menggunakan Pemrograman Linear Metode Simpleks Dan Softwere POM-QM - Agnes monika; Aldo Hartanto; Aprilia Silitonga (Jurnal Sosial dan Humaniora, 2026)
This study aims to optimize the profit from selling Chai Kue products using a linear programming approach with the simplex method. In the Chai Kue production process, limited resources such as rice flour, tapioca flour, and vegetables affect the quantity of each type of kue that can be produced. This research formulates a mathematical model consisting of a profit objective function and several constraints based on the availability of raw materials. The simplex method is applied to solve the model and determine the optimal production mix that maximizes profit. The analysis results show that by optimally allocating resources, business profits can be significantly increased. This study provides efficient production strategy recommendations for small-scale entrepreneurs to manage resources optimally.